Use of hyrax distractor in maxillary hypoplasia associated with cleft lip and palate patients - Neeraj Upadhyay; Arun Kumar Singh; Veerendra Prashad; Divya Narayan Upadhyaya (Wolters Kluwer Medknow Publications, 2019)
Context: Use of hyrax expander for palatal arch lengthening (anteroposterior) is not new, but large series with long-term follow-up is lacking. Aims: The aim of this study was to evaluate surgically assisted rapid maxillary expansion for hypoplastic maxilla, its efficacy, patient's satisfaction, and relapse rates. Settings and Design: A prospective study was done in PGD of Plastic Surgery, KGMU, Lucknow, between October 2014 and December 2015. Subjects and Methods: Fifteen patients with maxillary hypoplasia associated with cleft lip and palate underwent anterior segmental maxillary osteotomy. Distraction of anterior segment was done with a tooth-anchored hyrax expansion screw oriented in anteroposterior direction. Distraction was started on the 7th day. After desired advancement, the device was left intact for a consolidation period of 3 months and follow-up for any complication was done at the end of 6 months. Statistical Analysis Used: IBM SPSS version 20 software was used. Data expressed as number (percentage) and mean ± standard deviation, Student's t-test and ANOVA were used to compare mean between groups. Results: Bony landmarks sella-nasion-A point angle, maxillary length (ANS-PNS), mean space created on one side (mesial border of first molar to distal border of first premolar), and point A-N perpendicular improved significantly (P < 0.001). There was no significant change in vertical height of maxilla. Soft-tissue profile of patient (Sn-G perpendicular) also improved significantly (P < 0.001). No relapse was observed in patient during the 6 months of follow-up. Conclusion: Results of hyrax distractor in maxillary hypoplasia associated with cleft lip and palate patients were highly promising in patients with occlusal discrepancy <8 mm.